Effects of non-selective and size-selective fishing on perch populations in a small lake - Olin, Mikko Johannes; Tiainen, Joni Matias; Rask, Martti; Vinni, Mika Tapio; Nyberg, Kari Börje; Lehtonen, Hannu Väinö Tapani (Finnish Environment Institute, 2017)
Retaining large individuals is considered intrinsic to sustainable fishing. In this nine-year study, we explored the effects of simulated recreational fishing on life-history traits of two perch (Perca fluviatilis) populations in a lake divided for experimental purposes into two sections. In each section, one of the two following fishing methods was used: non-selective and negatively size-selective i.e. large individuals released. Non-selective fishing rapidly decreased the average size and age of the spawning perch stock thus reducing the average size of spawned eggs. Both fishing procedures increased the share of females in the spawning population due to decreased age at maturity. The average age at maturity decreased more in females than in males. The reductions in the density and biomass of the populations and increase in the growth rate of perch were temporary but the effects on size and age structure persisted throughout the study period. The retention of large individuals can delay the adverse effects of fishing on populations, and enable reproduction of large females, thereby sustaining high genetic variability and better quality of offspring. Peer reviewed